THE IMPLEMENTATION OF PUSHBACK PROCEDURE AND TAXI ROUTING AT THE APRON CARGO OF KUALANAMU INTERNATIONAL AIRPORT, DELI SERDANG: IMPLEMENTASI PUSHBACK PROCEDURE DAN TAXI ROUTING DI APRON CARGO BANDAR UDARA INTERNASIONAL KUALANAMU DELI SERDANG - MUHAMMAD CAESAR AKBAR; Surya Tri Saputra; Imam Sonhaji (Jurnal Penelitian)
Competition in the world of work is growing rapidly and human resources are also required to always develop self-competence, plus in the aviation world which currently continues to progress in the field of Aviation Technology which includes Computerized Technology, Radio Communication Technology, to Air Navigation tools that can support activities in the field of aviation. At this time, air transportation is one of the modes that help people to travel long distances. Therefore, services and facilities supporting the air transportation process need to be further improved both in terms of technology, standard procedures, human resources and adequate infrastructure. As with air traffic, all supporting factors must be considered as an effort to improve air traffic services. For better efficiency improvement efforts, namely by making Taxi Routing and Pushback Procedures for Apron Cargo because this can increase the efficiency and safety of air traffic for aircraft movement on the ground By issuing taxi routing apron cargo at the AIP of Kualanamu Airport and issuing Pushback Procedures for apron cargo at the AIP of Kuala Namu Airport